Walt Whitman & Edward Dowden : 1869-1886 - O'Brien, Denis Mark (Trinity College (Dublin, Ireland). School of English, 2002)
This literary history provides an extensive examination of Walt Whitman's reception in Ireland in the 1870s and 1880s, at a time when he was broadly vilified for poor artistry and obscenity in America and Europe. It reveals how Irish readers such as Edward Dowden, John B. Yeats, John Todhunter, Standish O'Grady and T.W.Rolleston shared an enthusiasm for the national, spiritual and democratic prophet who animated their "intellect" and "whole moral nature." To date, there has been no comprehensive assessment of their relationship with Whitman.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin